Developing Instructional Materials of Drama for English Language and Letter Students SMA Al-Miftah Palengaan-Pamekasan - listyowati, rini; Hanna, Ina Daril (Lingual Journal of Language and Culture; Vol 10 No 2 (2020): Lingual: Journal of Language and Culture, 2020)
The purpose of developing instructional unit to get: (1) instrcutional unit for Drama teaching materials students of SMA AL-MIFTAH Palengaan Pamekasan, (2) determine the validity/feasibility of the product. The expert assessment include: 1) assessing the learning content expert product Drama courses teaching materials with excellent qualification with a score of 92,5%, guide teacher 89,58%, guide students 83%; 2) instructional design expert assess product materials Drama courses 85%, guide teacher 87,5%, guide students 87,5%; 3) media expert assess learning materials product Drama courses 97,5%, guide lecture 100%, guide students 97,5%. The result of the expert review  as basis of further improvement of the products can be tested to get input from the users. The test includes: 1) an individual trial for four students with s score 88,7% and guide students 89,8%; 2) test for the small group of eight students, assess product of material s 90,4% and guide students 84.3%; 3) test for large group for 25 students evaluate teaching materials product  90,7% and guide students 84,3%. It can be concluded that product development is considered fit for using as a learning resource for language and letters department students of SMA AL-MIFTAH Palengaan Pamekasan.